Effects of 4 weeks of whole-body vibration training on energy expenditure during deep squats of male well-trained students - Huang, Xiaohan; Ye, Zhengyang; Qin, Xuelin (Frontiers in Physiology, 2023)
From the perspective of energy expenditure,this study investigated the effects of whole-body vibration training on energy metabolism of deep squats with different weights. Twenty-two healthy male college students with sports experiences , and they were randomly assigned to perform Resistance Exercise Vibration (REV) orResistance Exercise (RE) with varying loads 2 times per week for 4 weeks. Oxygen uptake and heart rate were measured before, during and after exercises using a gas analyzer, and energy expenditure was calculated.The results showed that: (1) the oxygen uptake and energy expenditure of the REV group were significantly higher than those of the RE group during and 30 min after exercise(p < 0.01), respectively.And the excess oxygen consumption (EPOC) was also significantly higher than that of the RE group(p < 0.01).(2) Changes in oxygen uptake and energy expenditure were stable with increasing exercise in both vibration and non-vibration conditions.There was no difference in energy expenditure per unit of body mass versus additional energy per kilogram of body weight ( p > 0.05 ) . (3) No significant differences in changing exercise intensity were observed in the REV group compared to the RE group during the adjacent incremental load phases of △ (40%-0%) and △ (80%-40%) of load during and 30 min after exercise(p > 0.05). Our results suggest that (1) vibration training can increase energy expenditure during low-intensity training and excess post-exercise oxygen consumption,as well as improve exercise intensity. (2) The effects on energy expenditure were the same for both weight-bearing and nonweight-bearing deep squats up to 40 % of body mass.